SARS-CoV-2 detection and sequencing in heart tissue associated with myocarditis and persistent arrhythmia: A case report. (2021) - Egas, Diego; Guadalupe, Juan José; Prado-Vivar, Belén; Becerra-Wong, Mónica; Márquez, Sully; Castillo, Stalin; Latta, Johanna; Rodriguez, Francisco; Escorza, Giovanni; Trueba, Gabriel; Grunauer, Michelle; Barragán, Verónica; et al.
Abstract: Background: SARS-CoV-2 uses the human cell receptor angiotensin-converting enzyme (ACE2). ACE2 is widely present in the cardiovascular system including the myocardium and the conduction system. COVID-19 patients that present severe symptoms have been reported to have complications involving myocardial injuries caused by the virus. Here we report the detection of SARS-CoV-2 by whole genome sequencing in the endocardium of a patient with severe bradycardia. Case presentation: We report a case of a 34-year-old male patient with COVID-19 tested by PCR, he started with gastrointestinal symptoms, however, he quickly deteriorated his hemodynamic state by means of myocarditis and bradycardia. After performing an endocardium biopsy, it was possible to identify the presence of SARS-CoV-2 in the heart tissue and to sequence its whole genome using the ARTIC-Network protocol and a modified tissue RNA extraction method. The patient's outcome was improved after a permanent pacemaker was implanted. Conclusions: It was possible to identify a SARS-CoV-2 clade 20A in the endocardium of the reported patient.